The role of implicit beliefs about emotions and emotion regulation on psychological adjustment: a study among youth athletes - Miguel Cunha; Rui Sofia; Cláudia Dias (Human Movement)
Purpose Youth psychological health and well-being are currently alarming. Young athletes face the same stressors as their non-athletic peers, in addition to unique challenges related to sports. This study aimed to understand the role of self-control and emotion regulation on the young athlete’s psychological well-being, while also considering the influence of implicit beliefs about emotions.